A control model of policy uncertainty and energy R&D investments. (1st April 2010) - Shittu, Ekundayo; Baker, Erin
Using an optimal control model, we explore the reaction of a firm's optimal investment into an R&D program that aims at non-carbon technologies under uncertainties about a future carbon tax. We find; first, that the influence of risk on investment decisions depends on model formulation. Second, near-term investments decrease in risk in the magnitude of a carbon tax, but increase in uncertainty in the timing of a carbon tax.